Failure of the EFL Classroom: Factors Affecting English Language Acquisition Schools - Ameen Alahdal, Fahad Saleh S. Alfallaj, Arif Ahmed Mohammed Hassan Al-Ahdal, (Opción, 2019)
The current study is an effort to highlight the aspects which contrarily affect learning outcomes in the EFL classrooms. The study was quantitative in nature and both EFL learners and teachers were taken in the loop in one way or another. The findings show that factors causing poor learning included less exposure to listening/speaking activities in daily life interaction, less language learning ability, age, previous knowledge, attitude, and motivation. In conclusion, opportunities for peer interaction were lacking in the classrooms, there was lack of motivation, hesitation in language use, lack of interaction with teachers in English and improper communication.